Controlling for Agricultural Land Conversion District in West Java Province Tasikmalaya - Ade Iskandar (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Population growth and economic and industrial development resulted in the degradation, fragmentation and conversion of agricultural land threatens the carrying capacity of the region both nationally and locally. Amount of conversion of agricultural land into non-agricultural land through regulation requires supervision by licensing, regulating and structuring. While the control is done by providing incentives in the form of tax incentives, compensation, cross-subsidies, development and procurement of infrastructure, facilities and public utilities as well as the ease of licensing procedures.